Simulator input-output sistem kontrol menggunakan Raspberry Pi - Zainal Bachrudin; Catur Edi Widodo; Kusworo Adi (Youngster Physics Journal, 2017)
In this research has been made I / O simulator which is a tool to simulate input and output of a control system using Raspberry Pi. Raspberry Pi has 26 GPIO (General Purpose Input and Output) pins that can be used to control inputs and outputs on the I / O simulator. The 26 GPIO pins are divided into two main systems, is 13 GPIO pins that are odd numbered as inputs and 13 other GPIO pins which are even numbered as outputs. The Raspberry Pi GPIO pins are ordered as inputs and outputs using Python programming languages. The command is done by reading the switch as input signal input, then Raspberry Pi process the input signal and send data as output signal with LED flame on the I / O Simulator. The I / O simulator can simulate logic gates, as AND, OR, NOT, and ADD, and can run mini distillation plant.Keywords: Simulation, Input-Output, Raspberry Pi, Python